2010
DOI: 10.2528/pier10072708
|View full text |Cite
|
Sign up to set email alerts
|

On the Scattering of Electromagnetic Waves by a Charged Sphere

Abstract: Abstract-Scattering of electromagnetic radiation by a charged homogeneous spherical particle/body is treated. Theoretical solution represents a generalization of the Mie's scattering theory for electrically neutral sphere. It is shown that classical and quantum physics approaches may lead to different conclusions, as documented by numerical computations assuming various permeabilities, refractive indices, surface charges, temperatures, and other physical parameters of the spherical particles. Two discrete wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Here, ε 0 is the permittivity of environmental medium, E h is the intensity of the environmental electric field at the location of sand, and H ðθ À θ 0 Þ is the Heaviside function [14]. In this paper we employed a spherical polar coordinate system with coordinates ðr; θ; φÞ and a rectangular coordinate system with coordinates ðx; y; zÞ; the corresponding unit base vectors are ðr; θ; φÞ and ðx; y; zÞ, respectively.…”
Section: The Polarization Chargementioning
confidence: 99%
See 1 more Smart Citation
“…Here, ε 0 is the permittivity of environmental medium, E h is the intensity of the environmental electric field at the location of sand, and H ðθ À θ 0 Þ is the Heaviside function [14]. In this paper we employed a spherical polar coordinate system with coordinates ðr; θ; φÞ and a rectangular coordinate system with coordinates ðx; y; zÞ; the corresponding unit base vectors are ðr; θ; φÞ and ðx; y; zÞ, respectively.…”
Section: The Polarization Chargementioning
confidence: 99%
“…Some theoretical models and various numerical techniques have been found to predict the optical properties of particles [3,4], but most of them have neglected the effects of the environment factors, except for the environmental humidity [5] and the adhesion of mineral and soot aerosols [6,7]. However, most particles of interest in astrophysics and atmospheric sciences are charged [8][9][10][11][12], and those electrified particles not only enhance the attenuation of incident EM wave [13][14][15][16][17][18][19][20], but also generate a strong Electrostatic field (signed as E-field for short). For example, the charged sands or dusts can produce a strong E-field in the air [21][22][23][24][25][26], and the maximal intensity can reach up to 200 kV/m [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…is the surface conductivity analogous to the (bulk) conductivity and it may be complex and depend on the frequency. Bohren and Hunt (Bohren and Hunt, 2011) and Klačka et al (Klačka and Kocifaj, 2007;Klačka. and Kocifaj, 2010) studied , usually expressed as = + .…”
Section: Rpr Of a Charged-particle Systemmentioning
confidence: 99%
“…Bohren et al theoretically studied the scattering of EM waves by a charged particle and found that the scattering coefficients of particles carrying 10 charges and neutral particles greatly differ (Bohren and Hunt, 2011). Klačka's research group later conducted a series of studies to investigate the scattering/absorption of dust particles, water droplets, and ice grains, finding that charges carried by the particles affect the optical properties of the particles and the scattering/absorption of EM waves when the particle size parameter (2 / , in which r is the particle radius and λ is the EM wavelength) is less than 0.01 (Klačka and Kocifaj, 2007;Klačka. and Kocifaj, 2010;Klačka et al, 2015).…”
mentioning
confidence: 99%
“…The generalized Lorenz-Mie theory (GLMT) developed by Gouesbet et al is effective for describing the interaction of a shaped beam with a spherical particle by relying on the separability of variables [1][2][3], and has been extended by so many researchers to multilayered spheres [4,5], spheroids [6] and infinite cylinders [7][8][9]. Various applications of focused beam scattering include optimizing the rate at which morphology-dependent resonances (MDRs) are excited, laser trapping, particle manipulation, and the analysis of optical particle sizing instruments [10,11].…”
Section: Introductionmentioning
confidence: 99%